2019
DOI: 10.1083/jcb.201905002
|View full text |Cite
|
Sign up to set email alerts
|

ALK4 coordinates extracellular and intrinsic signals to regulate development of cortical somatostatin interneurons

Abstract: Although the role of transcription factors in fate specification of cortical interneurons is well established, how these interact with extracellular signals to regulate interneuron development is poorly understood. Here we show that the activin receptor ALK4 is a key regulator of the specification of somatostatin interneurons. Mice lacking ALK4 in GABAergic neurons of the medial ganglionic eminence (MGE) showed marked deficits in distinct subpopulations of somatostatin interneurons from early postnatal stages … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2

Relationship

4
2

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 67 publications
0
11
0
Order By: Relevance
“…Given the wide range of expression ratios observed between Grik1 and other subtypes in Sst interneurons ( Figure S3C ), we asked if this variability was due to cell-by-cell differences or to distinct expression properties across Sst interneuron subtypes. To assess this, we plotted the expression ratios for Grik1 across six distinct subtypes of Sst interneurons ( Figure S3D ) ( Göngrich et al, 2020 ; Hilscher et al, 2017 ; Ma et al, 2006 ; Muñoz et al, 2017 ; Naka et al, 2019 ; Tasic et al, 2018 ). While subtle differences were observed in different Sst subtypes, including a clear bias toward higher Grik1 expression in the Chodl Sst interneurons, the generally broad profile of expression ratios was maintained across Sst subtypes.…”
Section: Resultsmentioning
confidence: 99%
“…Given the wide range of expression ratios observed between Grik1 and other subtypes in Sst interneurons ( Figure S3C ), we asked if this variability was due to cell-by-cell differences or to distinct expression properties across Sst interneuron subtypes. To assess this, we plotted the expression ratios for Grik1 across six distinct subtypes of Sst interneurons ( Figure S3D ) ( Göngrich et al, 2020 ; Hilscher et al, 2017 ; Ma et al, 2006 ; Muñoz et al, 2017 ; Naka et al, 2019 ; Tasic et al, 2018 ). While subtle differences were observed in different Sst subtypes, including a clear bias toward higher Grik1 expression in the Chodl Sst interneurons, the generally broad profile of expression ratios was maintained across Sst subtypes.…”
Section: Resultsmentioning
confidence: 99%
“…The functions of activin are mediated by activin-like kinase (ALK) receptor, of which ALK4 is the main receptor mediating activin signaling in human cells [88]. Mice lacking the ALK4 receptor in GABAergic interneurons exhibit substantial deficits in medial ganglionic eminence (MGE)-derived somatostatin-expressing interneurons, which represent 30% of all cortical GABAergic interneurons [89,90]. The development of these cells is controlled by various transcription factors, including SATB1 [91].…”
Section: Transcription Factors Regulating Somatostatin Expressionmentioning
confidence: 99%
“…The development of these cells is controlled by various transcription factors, including SATB1 [91]. Recently, Göngrich et al [89] demonstrated that SATB1 binds to different regions of the PISCES motif within the somatostatin promoter and that the activin signal alters this interaction from decreased binding to the distal region to increased binding to the more proximal region. Of note, activin does not increase somatostatin transcription, indicating that activin signaling is insufficient to regulate the expression of the peptide hormone.…”
Section: Transcription Factors Regulating Somatostatin Expressionmentioning
confidence: 99%
“…Mice were housed 2-5 per cage in standard conditions in a temperature and humiditycontrolled environment, on a 12/12 h light/dark cycle with ad libitum access to food and water. The following transgenic mouse lines were used for experiments: Gad67 Cre (Tolu et al, 2010), Nkx2.1 Cre (Xu et al, 2008), Gpr101 Cre (Reinius et al, 2015) and (Göngrich et al, 2020). All animals were bred in a C57BL6/J background (Jackson).…”
Section: Micementioning
confidence: 99%
“…A null mutation in mouse Acvr1b, the gene encoding ALK4, is embryonic lethal due to defects in primitive streak formation and gastrulation (Gu et al, 1998). Using a conditional approach, a recent study from our laboratory demonstrated a role for ALK4 in regulation of cortical somatostatin interneuron development (Göngrich et al, 2020). However, a large gap of knowledge remains on the functions of ALK4 in the nervous system, particularly in the adult brain.…”
Section: Introductionmentioning
confidence: 99%